Automated Prescription of Alcoholic Content to Dipsomaniac - C, Saranya; Surya, E; Priyaa K, Karpaga (International Journal of Engineering and Technology, 2018)
Alcohol addiction is an exponentially increasing dreadful disease. Alcoholic beverage is a drink that leads to greater risks of human health related problems. The consumption of alcohol is spring up as a serious issue. It makes a great difference on , bothÂ  â€œhow muchÂ you drink on any dayâ€ andÂ â€œhow oftenÂ you have a heavy drink,"Â The risk of developing alcoholism is not caused by a single gene, but rather numerous genes that interact with one another. Need of this paper is to reduce alcohol consumption by controlling and monitoring. Here we uses Sensors which response to a human physical stimulus and transmit a developed impulse. The interpreted data from the sensor is analyzed and used for prescribing the amount of liquor to the dipsomaniac person. The digital statistics is remotely maintained in the cloud repository. Through this alcohol sales, addiction can be controlled and avoid illegal sales. The intention of this paper is to monitor the health condition of a person.Â